Pengaruh Konsep Bauran Pemasaran terhadap Kepuasan Konsumen Dan Keputusan Membeli Produk Batik di Mageria Batik Malioboro - Darnawi Darnawi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2014)
The research aims to know how far the influence of marketing mix, consisting of product, price, location and promotion toward customer satisfaction and the impact to purchase decision of batik product at Margaria Batik in Malioboro Yogyakarta. The data was collected by spreading questioner to 150 respondents, chosen by purposive sampling and analyzed by path analysis method. The hypothesis was submitted are marketing mix has an influence effect to purchase decisions by direct or indirect pass through the customer satisfaction. The analysis result of the first sub-structure regression was known that product and price dimensions have significant influences on customer satisfaction. Whereas, the location and promotion dimension didn’t have significant influence on customer satisfaction. The analysis result of the second sub-structure was known that product and price have direct influences dominantly than indirect influences pass through the customer satisfaction.